The Gary Picture of Short-Wavelength Plasma Turbulence—The Legacy of Peter Gary - Narita, Y.; Parashar, T.N.; Wang, J. (Frontiers in Physics, 2022)
Collisionless plasmas in space often evolve into turbulence by exciting an ensemble of broadband electromagnetic and plasma fluctuations. Such dynamics are observed to operate in various space plasmas such as in the solar corona, the solar wind, as well as in the Earth and planetary magnetospheres. Though nonlinear in nature, turbulent fluctuations in the kinetic range (small wavelengths of the order of the ion inertial length or smaller) are believed to retain some properties reminiscent of linear-mode waves. In this paper we discuss what we understand, to the best of our ability, was Peter Gary’s view of kinetic-range turbulence. We call it the Gary picture for brevity. The Gary picture postulates that kinetic-range turbulence exhibits two different channels of energy cascade: one developing from Alfvén waves at longer wavelengths into kinetic Alfvén turbulence at shorter wavelengths, and the other developing from magnetosonic waves into whistler turbulence. Particle-in-cell simulations confirm that the Gary picture is a useful guide to reveal various properties of kinetic-range turbulence such as the wavevector anisotropy, various heating mechanisms, and control parameters that influence the evolution of turbulence in the kinetic range.